Long noncoding RNA SBF2-AS1 act as a ceRNA to modulate cell proliferation via binding with miR-188-5p in acute myeloid leukemia - Yun-Jiao Tian; Yan-Hua Wang; Ai-Ju Xiao; Pei-Ling Li; Jia Guo; Tuan-Jie Wang; Dong-Ju Zhao (Artificial Cells, Nanomedicine, and Biotechnology)
LncRNA SBF2-AS1 has been reported to be implicated in the deterioration of multiple human cancers. However, the roles and underlying mechanisms of SBF2-AS1 in acute myeloid leukemia (AML) are still unclear. In the present study, the online GEPIA database showed that SBF2-AS1 expression was significantly increased in AML samples. QRT-PCR results showed that SBF2-AS1 expression was upregulated in AML cells. CCK-8 assay revealed that SBF2-AS1 inhibition decreased AML cells proliferation ability in vitro. Flow cytometry assays showed that SBF2-AS1 inhibition induced AML cells apoptosis and arrested AML cells in G0/G1 phase. Mechanistically, miR-188-5p was identified as a direct target of SBF2-AS1. SBF2-AS1 upregulated the expression level of ZFP91 by sponging miR-188-5p. And the effects of SBF2-AS1 suppression on AML cells progression could be abolished by miR-188-5p inhibitors. Moreover, we found that SBF2-AS1 inhibition reduced tumor growth in vivo. Taken together, our findings elucidated that SBF2-AS1 could act as a miRNA sponge in AML progression, and provided a potential therapeutic strategy for AML treatment.